Life-Course Changes and Parent–Adult Child Contact. (September 2014) - Ward, Russell; Deane, Glenn; Spitze, Glenna
Despite increased interest in parent–adult child relations, there has been little attention to how these are influenced by changes in their lives, reflecting transitions and linked lives within a life-course perspective. Hybrid multilevel models are used to analyze the change in parent–adult child contact over two waves of the National Survey of Families and Households. Changes in parent–child proximity, parent and child marital status, and child parental status are associated with change in contact; continued coresidence with another adult child is related to contact with non-coresidential children; but change in parent health does not affect contact. Some patterns are stronger for daughters and biological children who tend to have stronger relationships with their parents. These analyses demonstrate how life-course transitions of parents and adult children can be examined in family context to understand how changes in the life of one family member may influence relations with another.